2001
DOI: 10.2337/diaspect.14.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Making a Difference With Interactive Technology: Considerations in Using and Evaluating Computerized Aids for Diabetes Self-Management Education

Abstract: This article provides a discussion of the strengths and limitations of interactive technologies (e.g., Internet, CD-ROM) as supplements to and extensions of diabetes self-management education. Examples are provided, and the RE-AIM framework is used to consider how different interactive technologies have been used to enhance the Reach, Effectiveness, Adoption, Implementation, and Maintenance of interventions. Appropriate use of these technologies (e.g., computer administration, scoring, and feedback on assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Interactive computer technology will be used increasingly in future research and practice (12,33). It is possible that greater benefit could be obtained through using interactive technology to address lifestyle change issues such as physical activity and nutrition counseling that are not often dealt with sufficiently in primary care (11,12,(33)(34)(35) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interactive computer technology will be used increasingly in future research and practice (12,33). It is possible that greater benefit could be obtained through using interactive technology to address lifestyle change issues such as physical activity and nutrition counseling that are not often dealt with sufficiently in primary care (11,12,(33)(34)(35) …”
Section: Methodsmentioning
confidence: 99%
“…We report a "practical clinical trial" (10) to improve diabetes care, characterized by a clinically relevant intervention, a diverse sample of patients recruited from heterogeneous practices, and end point data on a broad range of outcomes (10,11). Our purpose is to describe outcomes important to patients, clinicians, and policy makers derived from typical community settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Common approaches to providing this additional self-management support include telephonebased counseling (7)(8)(9)(10)(11)(12), group medical visits (13)(14)(15)(16)(17)(18)(19)(20)(21), and, increasingly, computer or internetbased programs (22)(23)(24)(25)(26)(27)(28)(29)(30). Efficacy studies of self-management support have shown improvements in patient satisfaction, healthy behaviors, self-efficacy, and, in some cases, utilization and clinical outcomes (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…A number of modalities can be incorporated to achieve these activities, such as computer interactive software or tailored print materials, and telephone support can be used to efficiently accomplish intervention components. [45][46][47] These principles or guidelines can be integrated into most practices. The integration that will work best in a specific setting is probably best determined through a series of rapid cycle improvement tests (mini studies where new conditions and strategies are completed with a few patients and compared with standard care).…”
Section: Recommended Assessment and Brief Intervention Activitiesmentioning
confidence: 99%